2008
DOI: 10.1074/jbc.m804613200
|View full text |Cite
|
Sign up to set email alerts
|

CDKL5 Expression Is Modulated during Neuronal Development and Its Subcellular Distribution Is Tightly Regulated by the C-terminal Tail

Abstract: Mutations in the human X-linked cyclin-dependent kinase-like 5 (CDKL5) gene have been identified in patients with Rett syndrome (RTT), West syndrome, and X-linked infantile spasms, sharing the common feature of mental retardation and early seizures. CDKL5 is a rather uncharacterized kinase, but its involvement in RTT seems to be explained by the fact that it works upstream of MeCP2, the main cause of Rett syndrome. To understand the role of this kinase for nervous system functions and to address if molecular m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
219
3
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 172 publications
(249 citation statements)
references
References 41 publications
14
219
3
2
Order By: Relevance
“…20 CDKL5 levels were found to be low in the embryonic cortex and strongly induced at perinatal and postnatal stages in maturing neurons residing in both cerebral cortex and hippocampus until day P14, where after it declines. 12 A detailed analysis of Cdkl5 expression in adult mouse brain (Allen Brain Atlas) showed that its mRNA levels are particularly high in the adult forebrain, 13 consistent with its role in neuronal maturation. 12 Conversely, isoform II, transcribed from exons 1a and 1b (but not exon 1), is only expressed at very low levels in human fetal brain and testes.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…20 CDKL5 levels were found to be low in the embryonic cortex and strongly induced at perinatal and postnatal stages in maturing neurons residing in both cerebral cortex and hippocampus until day P14, where after it declines. 12 A detailed analysis of Cdkl5 expression in adult mouse brain (Allen Brain Atlas) showed that its mRNA levels are particularly high in the adult forebrain, 13 consistent with its role in neuronal maturation. 12 Conversely, isoform II, transcribed from exons 1a and 1b (but not exon 1), is only expressed at very low levels in human fetal brain and testes.…”
Section: Discussionmentioning
confidence: 93%
“…12 A detailed analysis of Cdkl5 expression in adult mouse brain (Allen Brain Atlas) showed that its mRNA levels are particularly high in the adult forebrain, 13 consistent with its role in neuronal maturation. 12 Conversely, isoform II, transcribed from exons 1a and 1b (but not exon 1), is only expressed at very low levels in human fetal brain and testes. 46,47 It remains to be determined in what brain compartment(s) and in which cells this isoform is predominantly expressed.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…As truncations of the C-terminus seem to enhance autophosphorylation and kinase activity of CDKL5 and cause its nuclear accumulation and activity, it has been suggested that these sequence variations may be pathogenic. 11 On the basis of this line of evidence, a nonsense mutation p.Arg970X (c.2908C4T) was reported in 2009 in a girl, suggestive of 'atypical' Rett syndrome (severe intellectual disability, microcephaly, poor eye fixation, stereotypies, not able to walk, breathing irregularities, mild seizures at 17 months of age) but without regression, and was suggested to be pathogenic. 2 Although the p.Arg970X was not found in the mother of the proband, DNA analysis in her father and a further functional study were not performed.…”
Section: Discussionmentioning
confidence: 99%
“…At the protein level, the N-terminal domain is involved in the catalytic activity of the protein, whereas the C-terminal region may regulate its subcellular localization. 6,23 CDKL5 phosphorylation targets are currently largely unknown. So far, it has been shown that the protein, in vitro, may autophosphorylate, and it phosphorylates the product of the methyl-CpG-binding protein 2 (MECP2, OMIM 300005) gene, which is mutated in 490% of classic RTT patients, 24 suggesting a common signaling pathway between these two proteins; 6,9,25 and the N-terminal region of the DNA methyltransferase 1 in nuclei.…”
Section: Introductionmentioning
confidence: 99%